Hubungan Antara Profesionalitas Dosen, Penilaian Kinerja Dosen Oleh Mahasiswa, Dan Motivasi Mahasiswa - Agung Parmono; Aminatus Zahriyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The achievement of the goals of the teaching and learning process in a university is inseparable from the role of lecturers and students. The activeness of lecturers in providing lectures and the activeness of students in participating in the teaching and learning process are the main keys to the success of the teaching and learning process, in this study using the analysis of the Structural Equation Model with five endogenous variables X, one moderating variable Y and one exogenous variable Z. 2) Knowing that there is an influence between the professionalism of lecturers and the motivation of Sharia Accounting students. Therefore, the results of variables that are part of student assessment of lecturer performance Teaching readiness, teaching materials, teaching discipline, teaching evaluation, lecturer personality are not factors that affect the professionalism of sharia accounting lecturers IAIN Jember. From the results of data analysis using the Structural Equation Model , it was found that the professionalism of lecturers did not affect the motivation of students in the Sharia Accounting Study Program.